Coral Reef Ecosystem Sensitivity Study to Waste Pollution: Case Study of Karimun Jawa Islands - Rahman, Muhammad Arkan Zaky; Yulianto , Gatot; Kurnawan, Ferry (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
The coral reef ecosystem on Karimunjawa Island has an important ecosystem service value for the socio-economic life of the community. The many tourism activities result in pollution in the waters that can disrupt and even damage the balance of the coral reef ecosystem. This study was conducted to determine the extent of the impact of pollution caused and to develop an appropriate coastal pollution management strategy in overcoming pollution problems due to waste disposal activities. The method used in the study is the exploratory descriptive method. The exploratory descriptive method is a research method that is observational of an object in its natural environment, without any treatment of the object being studied. Data collection was carried out at 4 research locations, namely Tanjung Gelam, Karimunjawa, Batulawang and Sntok. The study can be analyzed using the CPCE (Coral Point Count with Excel) method. This method is used to determine the condition of coral reefs at a location. The highest value was obtained at the Sintok location while the lowest condition was on Karimunjawa Island. The average percentage summarizes live corals included in the moderate to very good category ranging from 23.89% - 77.67%. The results of the analysis show that in the horizontal cross-section the condition of the coral reef is better compared to the vertical condition. The weight of waste in the coastal area is highest in the Karimunjawa area and the least is in the Sintok Island area.